Microminerais biocomplexados em dietas para gatos em crescimento - Reis, Jéssica Santana dos (2016)
Studies with other species suggest that proteinate trace elements can substitute, in small amounts, inorganic supplements in growing cat diets. Thus, for conducting the present study, 30 kittens with 80 days of age were used in order to determine the effects of inorganic vs. bio-complexed sources and the supplement decrease of bio-complexed copper (Cu), iron (Fe), manganese (Mn), selenium (Se) and zinc (Zn) over performance, hematological and metabolism parameters and mineral status, for a period of 140 days. Inorganic trace elements (ING) were compared to four levels of bio-complexed minerals (BIO) under the form of proteinates (Bioplex ® TR Se). The diet 100%ING was supplemented with 8.4 mg Cu/kg (sulfate), 80 mg of Fe/kg (sulfate), 4.8 mg of Mn/kg (sulfate), 0.30 mg Se/kg (selenite) and 75 mg of Zn/kg, based on recommendations of the National Research Council (NRC). The Bioplex ® TR Se was used as substitute in the same mineral concentrations (100%BIO) or in smaller amounts (80%BIO, 60%BIO and 40%BIO) in the remaining diets, totalizing five treatments. The kittens were fed the diets during 140 days in a completely randomized design, totalizing six replicates per treatment. No difference (p>0.05) was observed between the ING and BIO sources for body weight, regarding the different levels; daily food intake; withers height; body length; fur growth; mineral bone density; fecal excretion of Fe and Se; absorption, urinary excretion, retention and skin concentration of Cu, Fe and Zn; concentration of Cu, Fe, Se and Zn in the gonad; Fe and Zn in the fur; Cu, Fe, Se and Zn in the plasma; activity of the enzymes SOD, GPx and alkaline phosphatase; plasma levels of malondialdehyde (MDA); serum Fe; concentration of transferrin; latent capacity and total Fe linkage; transferrin saturation index; blood count (except for mean corpuscular hemoglobin – MCH), leucocytes and total lymphocytes. We verified difference between the sources (p<0.05) for the concentration of Cu and Zn in feces; absorbed Se, on urine and skin; concentration of Mn in the gonad; Cu, Mn and Se in the fur; and ceruloplasmin activity. In conclusion, supplementation of up to 40% of the levels of Cu, Fe, Mn, Se and Zn recommended by the NRC (2006), in the form of proteinate (Bioplex ® TR Se), during the growth phase of cats, does not negatively affect their performance, metabolic parameters and mineral status.